Expression of Transferrin Protein and Messenger RNA in Neural Cells from Mouse and Human Brain Tissue - Eriko Abe; Takashi J. Fuwa; Kyoka Hoshi; Takashi Saito; Takenobu Murakami; Masakazu Miyajima; Norihiro Ogawa; Hiroyasu Akatsu; Yoshio Hashizume; Yasuhiro Hashimoto; Takashi Honda (Metabolites, 2022)
Iron is an essential nutrient in the body. However, iron generates oxidative stress and hence needs to be bound to carrier proteins such as the glycoprotein transferrin (Tf) in body fluids. We previously reported that cerebrospinal fluid contains Tf glycan-isoforms that are derived from the brain, but their origins at the cellular level in the brain have not yet been elucidated. In the present report, we described the localization of Tf protein and mRNA in mouse and human brain tissue. In situ hybridization of mouse brain tissue revealed that Tf mRNA is expressed by different cell types such as epithelial cells in the choroid plexus, oligodendrocyte-like cells in the medulla, and neurons in the cortex, hippocampus, and basal ganglia. In contrast, Tf protein was barely detected by immunohistochemistry in hippocampal and some cortical neurons, but it was detected in other types of cells such as oligodendrocyte-like cells and choroid plexus epithelial cells. The results showed that Tf mRNA is expressed by neural cells, while Tf protein is expressed in different brain regions, though at very low levels in hippocampal neurons. Low Tf level in the hippocampus may increases susceptibility to iron-induced oxidative stress, and account for neuron death in neurodegenerative diseases.